Hubungan Pengaturan Emosi Positif dengan Kecemasan Menjelang Menopause pada Perempuan Pekerja - Syarifah, Maftukhatus; Kusumaputri, Erika Setyanti (Universitas Ahmad Dahlan, 2014)
ABSTRACTThis research is aimed at explaining the relationship between positive emotion management and pre-menopause anxiety experienced by female workers. The subjects of this research are female workers who are in pre-menopause age range in Kalirejo Village, Salaman, Magelang, Central Java. The data of this research were gained by using positive emotion management scale and premenopause anxiety scale. The technique analysis used in this research was the product moment correlation. The analysis using correlation analysis technique resulted in R equivalent to -0,305, R2 equivalent to 0.093 with p = 0.003. Those results show that there is indeed a significant relationship between positive emotion management and female workers’ pre-menopause anxiety in Kalirejo village, Salaman, Magelang, Central Java. R2 equivalent to 0.093 shows that positive emotion management has a significance as much as 9,3% to female workers’ pre-menopause anxiety.Key words : female worker, pre-menopause anxiety, positive emotion management,